(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The urgency to retrieve memory in many Arab women’s writings becomes the impetus to retell the stories of women silenced, marginalized, and excluded by their own communities. There is no doubt that with the retrieval of memory comes the resituating of the body from its condition as an object of male desire, and its transformation into a desiring force that rejects its subjugation to a narrative of erasure (Fayad 148). Hanan Al Shaykh’s The Story of Zahra is divided into two books. The first book is entitled The Scars of Peace. In it we find the central female character, Zahra, is silently victimized by the patriarchal structure through its variously ugly manifestations. The second book is subtitled The Torrents of War. Here we find a completely different character, one who is ready to do anything to stop the war, even if it takes a relationship with a sniper – a symbol of patriarchal war – which ends in her tragic death.